Digital-based Performance Management Concept Within an Effort to Improve Employee Performance BUMDes During the Covid-19 Pandemic - Putu Agus Adnyana; Ni Made Rianita; Ni Luh Sri Kasih (Universitas Pendidikan Ganesha, 2021)
During the Covid-19 pandemic, many businesses or organizations complained because of the decrease in revenue turnover of the organization or its company, in addition, with the implementation of Work from Home (WFH) by the government while hampering employee performance in terms of serving or improving productivity. The purpose of this research is to know the performance of employees through the concept of work management and digitization as the main key to improving the performance of BUMDes employees in Buleleng Regency. The concept of performance management is the employee's activity and the employee's work is in line with the organization's objectives. This contributing to improve the performance of BUMDes. The research population is all BUMDes active in Buleleng Regency. Sampling in this study using random sampling techniques. The data analysis technique used in this study is Component based SEM analysis method, Partial Least Square (PLS). The results showed that the concept of Work Management has an effect on digitalization and employee performance. by increasing employee performance, then BUMDes will contribute better in service and increase the village's original income (PAD) so as to achieve the vision of BUMDes mission in the village in Buleleng Regency, BUMDes can maintain the coexistence and maximize performance during the pandemic covid-19 at the BUMDes to be able to explore and develop the economic potentials of the village, increase (PAD) and provide the best service in meeting the economic needs of the village community.